(untitled) (Global Journals of Research in Engineering, 2024)
Energy Transition from fossil fuel derived power sources to that of clean renewably sourced electricity enabling total electrification has emerged as the overriding challenge for humankind in the first quarter of the 21st century Ensuring energy security adapting to climate change and embracing the low carbon economy were among the critical factors for this paradigm shift Soft revolutions in renewable generation battery storage and power electronics technologically enabled the energy transition to clean electricity A pivotal advance in total electrification of our society empowering the electricity value chain is propelling the rapid transformation of the existing power grid into the Future Grid This global evolutionary development based on a combination of techno-economical and psycho-social understanding of electricity systems is seen as an absolute priority target in the current decade An expected goal and result of this development is that alternate current AC direct current DC grids merge